Teaching Methods Used in Primary Education for Making Physical Education Class More Effective - G. Bădicu (OVS LLC, 2018)
The objective is to demonstrate the importance of games that involve movement and of applicative pathways planning for making the class of physical education and sports in primary education more effective. Materials and methods. The participants in the research were 52 pupils (males: n=28 and females: n=24). The experiment was carried out between November 2016 and May 2017, at Andrei Mureşanu High School in Brasov county. In order to optimize physical education classes, we used dynamic games and applicative pathways throughout the research and within the instructive and educational process. Results. The average of the results of the final tests highlighted statistically significant differences compared to the initial test, for all students taking part in the experiment, with a materiality threshold of p<0.05. Conclusions. The experiment showed that the final scores achieved by the experimental group were much higher compared to the initial test. The use of movement games and applicative pathways led to an increased attractiveness of physical education classes, as the pupils took more pleasure in taking part in the teaching process. During the physical education class, teachers should use as many dynamic games as possible, as well as applicative pathways, routes etc., taking into account the positive effects that these factors have on the attractiveness of the teaching process. It is also important to take into consideration children's physical and psychological characteristics when organizing these activities.